Implementasi Peraturan Daerah Nomor 3 Tahun 2016 Tentang Penyelenggaraan Jaminan Kesehatan Daerah Kota Palangka Raya - Laksminarti Laksminarti; Gunawan Gunawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The Social Service Office of the City of Palangka Raya is one of the services in the City Government of Palangka Raya. One of the functions of the Social Office is as the implementer of regional regulation No. 3 of 2016 Implementation of the Regional Health Insurance for the City of Palangka Raya. This is because health insurance is one of the basic needs of the people of Palangka Raya City so that this is interesting to study. Sources of data in this study are primary data in the form of observations and interviews of Palangka Raya City Social Service Officers and the general public and other data supporters. Data collection techniques are observation, interview, documentation. The data analysis technique is data reduction, data presentation, conclusion drawing, and data verification. This research was conducted at the City Office of Palangka Raya using descriptive qualitative methods. The results of this study are that with existing limitations, the Social Service still strives to provide the best service for the community. The structure of the bureaucracy is running well, communication is running smoothly both internally and externally, the disposition is well run and resources are also good in providing services to the public. From these results, it can be said that the Social Service Office was able to implement Perda number 3 of 2016 quite well even though there were several obstacles/obstacles. Inhibiting factors have not been implemented properly Regional Regulation No. 3 of 2016 concerning the Implementation of Regional Health Insurance in Palangka Raya, among others: 1) Limited resources in particular Human Resources (HR) in the City of Palangka Raya Social Service, 2). Limited access to the community so that existing databases are sometimes prone to errors. 3). Limited supporting facilities and infrastructure, in this case, is signal coverage and wifi facilities that cause online services to be often delayed.